Monitoring System for Temprature, Humidity, and Ammonia Gas in Laying Hens Cages Based on Internet of Things - Fathur Ramadhan, A.M.; Zulhajji, Zulhajji; Haripuddin, Haripuddin (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study focuses on the development of an Internet of Things (IoT)-based monitoring system designed to measure and control temperature, humidity, and ammonia gas levels in laying hen cages to enhance environmental management efficiency, animal welfare, and productivity. The research employs a Research and Development (R&D) method using a prototyping model conducted at UD. Ayam Ras Petelur, Gowa Regency, Indonesia. The developed system integrates DHT11, and MQ-135 sensors connected to an Android application via NodeMCU ESP8266 and Firebase, enabling real-time monitoring, visualization, and remote access. Through this integration, farmers can instantly obtain environmental data, receive notifications when parameters exceed safe thresholds, and take immediate corrective actions to maintain optimal conditions for the chickens. Evaluation based on the ISO 25010 quality model shows that the system achieves 100% functional suitability and 92.6% usability, which indicates excellent performance and high practicality for end users. Sensor accuracy testing reveals reliability rates of 97.37% for temperature, 97.83% for humidity, and 95.50% for ammonia gas concentration, confirming the system’s precision and consistency in data measurement. The results demonstrate that the IoT-based monitoring system developed in this study is highly feasible, efficient, and accurate for real-time management of poultry cage environments. Overall, this research contributes to the adoption of smart farming technologies in Indonesia’s poultry industry, promoting data-driven decision-making and sustainable livestock management practices.